(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1989)
The new genus Kocaelia, with Aspidites toulai (Arthaber) as a type species, is here described. Based on the involute and compressed shape, occurrence of straight to slightly sinuous ribs and subammonitic suture in mature individuals the genus Kocaelia is attributed to family Beyrichitidae. The complex ontogeny distinguishes the genus Kocaelia from other closed genera.